2010
DOI: 10.1002/hlca.200900448
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of the 5,6‐Dihydro‐4H‐furo[2,3‐c]pyrrol‐4‐one Skeleton: A New Class of Compounds

Abstract: We hereby report the first preparation of the 5,6-dihydro-4H-furo[2,3-c]pyrrol-4-one (3) and its derivatives starting from methyl 3-(methoxycarbonyl)furan-2-acetate (8). The ester functionality connected to the methylene group was regiospecifically converted to the desired monohydrazide 9. Conversion of 9 into the acyl azide 10 followed by Curtius rearrangement gave the corresponding isocyanate derivative 11 (Scheme 2). Reaction of 11 with different nucleophiles produced urethane and urea derivatives (Scheme 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recently, we reported that the reactivity of the ester carbonyl groups in similar systems are different. 23 The ester functionality adjacent to the CH 2 group is more reactive than the other. Therefore, the regiospecific hydrolysis of the ester functionalities in 11a-c was possible.…”
mentioning
confidence: 99%
“…Recently, we reported that the reactivity of the ester carbonyl groups in similar systems are different. 23 The ester functionality adjacent to the CH 2 group is more reactive than the other. Therefore, the regiospecific hydrolysis of the ester functionalities in 11a-c was possible.…”
mentioning
confidence: 99%